Child emergency as a subject of rights in Child Education - Ana Katia Alves Santos (Universidade Federal de Santa Catarina, 2017)
The present text has the objetive of presenting systematized reflections after completion of an extension course (ACCS - Curricular Activity in Community and Society) named 'Childhood and Youth: Ethics of human preservation, citizenship and education in the 21st century with EDCH code 072, In the Faculty of Education of the Federal University of Bahia, and counted on the updated contribution, in 2017, of teachers in formation in the curricular component of EDC308 code of relational thematic. The central theme is the emergence of the Child as a Rights Subject in Early Childhood Education, based on the recognition of the need to effectively implement the Child and Adolescent Statute (ECA) and other legal instruments related to guaranteeing the rights of children. In the search for deepening, and reaching answers, the founding methodology is of a qualitative nature with focal group technique. The theoretical basis is based on RAYO (2004), SANTOS (2006), MARCÍLIO (1998), JARES (2002) among others.